AB0391 Sleep disorders in systemic lupus erythematosus patients: a cross sectional study. (23rd January 2014) - Tani, C.; Palagini, L.; Carli, L.; Signorini, E.; Vagnani, S.; Querci, F.; Gemignani, A.; Ciapparelli, A.; Bruno, R. M.; Ghiadoni, L.; Bombardieri, S.; Mauri, M.; et al.
Abstract : Background: Sleep disturbances are frequently observed in rheumatic diseases and significantly affect the quality of life of patients. The prevalence and characteristic of sleep disturbances in Systemic Lupus Erythematosus (SLE) are poorly studied. Objectives: This study aimed at evaluating both prevalence of sleep disorders and sleep quality in a cohort of SLE patients in comparison with patients suffering from a chronic disease as hypertension. Methods: In this cross-sectional study, 81 consecutive SLE patients were recruited from January 2012 through December 2012. The Pittsburgh Sleep Quality Index (PSQI), the Beck Depression Inventory (BDI) and the Self-Rating-Anxiety Scale (SAS) were administered to all subjects. Socio-demographic data were collected and a rheumatologic assessment was performed including disease activity and damage scales (European Consensus Lupus Activity Measurement, ECLAM, and Systemic Lupus International Collaborating Clinics Damage Index, SLICC-DI, respectively). the type of organ involvement, comorbidities and ongoing treatments were also recorded. A control group of 44 hypertensive (H) age and sex matched patients have been evaluated with PSQI, BDI and SAS rating scales. Results: Of the entire SLE cohort (mean age 43.5± 11 years; mean disease duration of 15.5±7.8 years), 8.6% had secondary antiphospholipid syndrome and 116% a secondary fibromyalgia. A history of neuropsychiatric involvement was present in 13.6% and renal involvement in 43.2%. The disease was active (ECLAM >2) in 11.1%, and disease damage (SLICC-DI ≥1) was observed in 38.2% of the patients. The mean PSQI score resulted 7, 2+3, 6 in SLE patients versus 7, 8+8, 1 in H group. Insomnia was observed in 64% SLE vs 54, 5% H patients: respectively 27.2% SLE patients had difficulties in initiating sleep vs 34, 1% H patients and 65.4% vs 36, 4% (p<0.05) have difficulties in maintaining sleep and/or early morning awakening. Mean SAS was respectively 24, 8+14, 7 vs 30.2+12, 7 and mean BDI was 5.9±8 vs 3, 7+5, 6. An anxiety disorder was more common in H patients with a prevalence of 34.1% vs 17.3% SLE (p<0.01); on a contrary a depressive disorder was present in 34.6% of SLE vs 22% H patients (p<0.05). In SLE group sleep disorders resulted significantly associated with higher BDI scores (p<0.0001) and higher educational level (p<.05). Difficulties in initiating sleep were related with disease duration (p<0.05) while no other associations with disease-related variables were found. Conclusions: In this cohort of SLE, sleep complaints, especially difficulties in maintaining sleep and/or early morning awakening, are more common than in H patients. In SLE, disease duration and depression seems to be associated with sleep disorders while in H an anxiety disorder seems more common. These data highlight the importance of investigating sleep disorders and depressive symptoms in SLE patients even when disease is in remission, in order to identify undiagnosed psychopathological disorder that need to be referred for a specialist evaluation. Disclosure of Interest: None Declared